IMPLEMENTASI NILAI-NILAI DASAR EKONOMI SYARIAH DALAM TRANSAKSI JUAL BELI PADA PEDAGANG MUSLIM DI PASAR RABU KECAMATAN GALING KABUPATEN SAMBAS : The purpose of the research is expected to create the growth of ethical entrepreneurial spirits. As a people, we know and understand what values should be practiced in carrying out trading activities. - Eva CLaudia Boru Lubis, Eva Claudia Boru Lubis; Sulia Sukmati, U; Iva Ashari Ananda (Sebi : Studi Ekonomi dan Bisnis Islam, 2024)
This research, using a descriptive qualitative approach, and includes the type of field research (field research). The data collection techniques used were observation, interviews and documentation. The primary source of data used is Muslim traders in Pasar Rabu. Research data analysis techniques are data reduction, data presentation, drawing conclusions. The data validity technique used is triangulation. The results of this study are 1). The understanding of traders related to the basic values of the Islamic economy in buying and selling transactions in the Wednesday Market is fully aware and understands in carrying out every transaction to buyers can be seen from the value of tawhid in terms of goods traded is always relying on halal and good buying and selling. As for the value aspect of adl (fairness), it is found that traders always instill the principle of fairness, which can be seen not looking at differences in social status to buyers in giving prices. Then the value of nubuwwah can be said that traders trade in accordance with the Quran and what is taught by the Prophet such as being polite, trustful, honest, open to a condition of goods without hiding a defect. For the value of the khilafah itself that every carrying out a buying and selling activity in the market cannot be separated from the form of interference and supervision of related parties in order to minimize fraud in order to create a safe and controlled market atmosphere. As for the value of ma'ad (results), every benefit from the results of trading from these results can lead to goodness and blessings in the world and in the hereafter. The application of Islamic economic values in trading has been fully implemented. The application carried out in the form of every action taken by traders in the Wednesday Market in selling goods always applies the concept of buying and selling halal and good, carrying out trade by prioritizing the blessings of the world and the hereafter